1991
DOI: 10.1159/000243365
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and D Activities in Intestinal Mucosa during Postnatal Development in Pigs. Relation to Intestinal Uptake and Transmission of Macromolecules

Abstract: The mucosal activities of cathepsin B and D were assayed in the small intestine of newborn pigs and of pigs 24 h, 6 days and 4–8 weeks old, respectively. Before sacrificing these animals, the intestinal capacity to internalise and further transmit macromolecules into the blood serum was evaluated by feeding a marker solution containing bovine IgG, bovine serum albumin and fluorescein-isothiocyanate-conjugated dextran 70,000 (FITC-dextran). No significant differences in the activities of cathepsin B or D were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Nineteen days after birth, the fetal type of enterocytes change to the adult type of enterocytes, which have the capacity to actively digest and absorb nutrients in the solid form of food [42]. From 24 to 36 h after birth, the transfer of macromolecules from the intestinal epithelium into the blood is decreased dramatically [43]. Gut closure is associated with the postnatal replacement of fetal intestinal enterocyte with the more mature cells that are incapable of internalizing macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen days after birth, the fetal type of enterocytes change to the adult type of enterocytes, which have the capacity to actively digest and absorb nutrients in the solid form of food [42]. From 24 to 36 h after birth, the transfer of macromolecules from the intestinal epithelium into the blood is decreased dramatically [43]. Gut closure is associated with the postnatal replacement of fetal intestinal enterocyte with the more mature cells that are incapable of internalizing macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although we observed that the ratio between intestinal membranebound and soluble CP activities was the same as that between membrane-bound and soluble CPH [26], it is worth noting that two distinct enzymes with di¡erent optimum pH values and behavior towards activators and inhibitors were found to exist in hog intestine. The soluble CP activity was probably due to cathepsin B, a cysteine enzyme of lysosomal origin with several endo-and exopeptidase activities [51,55] usually found in the gastroduodenal mucosa [56,57]. This enzyme, which is not a metallocarboxypeptidase, was not further characterized in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Zhang et al (1997) showed that the carbohydrate absorption is significantly low in the distal region in piglets (0-24 h) and Fan et al (2001) measured a significantly high level of aminopeptidase N in brush border membrane vesicles from the distal region in 1-to 2-week-old piglets. After gut closure catheptic activity as well as uptake of macromolecules was still measured in the distal region (Ekström and Weström, 1991). This could explain the more permanent appearance (over 6 days) of the vesicles in the distal region.…”
Section: Discussionmentioning
confidence: 97%